HISTOPATHOLOGY OF THE SPLEEN OF LAYING HENS POST-VACCINATION AVIAN INFLUENZA H5N1 ISOLATE FROM BALI - Wardani, Putu Intan Kusuma; Kencana, Gusti Ayu Yuniati; Winaya, Ida Bagus Oka; Supartika, I Ketut Eli (Buletin Veteriner Udayana, 2022)
Avian Influenza H5N1 belongs to a group of strategic infectious diseases and is a deadly zoonosis in both infected animals and humans. One of the main strategies for preventing AI in Indonesia is vaccination. The effectiveness of the AI ??vaccine will be better if the virus strain in the vaccine used is homologous to the viral strain in the field. This study aimed to determine the histopathology of the spleen of laying hens after AI-H5N1 vaccination isolates from Bali with the parameters of the diameter of the lymphoid follicles of the white pulp of the spleen. A total of 36 laying hens of the Novogen Brown strain were used for the research sample. The sample was divided into 2 groups, namely P0/control group without treatment and P1 group with AI-H5N1 vaccination treatment, isolate from Bali. Each group consisted of 18 laying hens. Chickens are reared since the age of 1 day. Vaccination was carried out after the chickens were 5 weeks old and boosted at 10 weeks with a vaccine dose of 0.5 ml/bird. Sampling of the spleen was carried out three weeks after booster for histopathological preparations. Data from the histopathological examination of laying hens spleen were analyzed by t-test. The results of the measurement of the spleen organ showed that the average diameter of the spleen white pulp lymphoid follicles of laying hens treated with AI-H5N1 vaccination isolates from Bali had a larger diameter than the unvaccinated group of chickens. The conclusion from this study was that AI-H5N1 vaccination from Bali isolates had a significant effect on increasing the diameter of the white pulp lymphoid follicles of the spleen of laying hens after vaccination.